Features of the organization and management of venture business - Unerbaeva, R. U.; Sharapiyeva, M. D. (Journal of Economic Research & Business Administration, 2015)
This article consists of theoretical aspect of business venture. A business venture is a start-up enterprise that is formed with the expectation and plan that a financial gain will result. Many refer to a business venture as a small business, since it normally starts out with an idea that begins with a small amount of capital or finances. Most business ventures are backed by one or more investors with the hope that the business will be profitable. In general, a business venture is born out of a need for something lacking in the current market. This need can be a service or product that consumers are asking for or need to serve a particular purpose. Once the need is identified, the business venture can be started by a smart investor or small business person that has the resources and time to develop and market the new commodity on the open market. A business venture will most likely be funded initially by an investor, which is often the small business owner or the originator of the idea. Once the business is created, other investors may get involved by providing support and venture capital to fund further development and increase awareness of the business venture with the intention of a higher profit being shared by all investors. In this scenario, the organization is actually a shared business venture, in that more than one party is involved in the process. In the beginning of a business venture, it is recommended that a formal business plan be written in order to outline the purpose and mission of the business for the future.Venture business is derived from science, basic and applied, and was born as a requirement of economic development as a missing link between science and industry. Mission to create clusters of high technology and innovative business venture does.Venture Capital is a leading creative part of the wave of the innovation process, so to speak of his system kernel.